Corporate governance and financing Choices in firms: a panel data analysis Of Sri Lankan companies - Balagobei, S. (My University, 2020)
An important financial decision facing firms is the choice between debt capital and equity capital. The financial structure of a firm is a specific mixture of debt and equity the firm uses to finance its operations. The financing choice of firms is crucial for any business organization. This paper investigated how corporate governance indicators such as board size, board independence, CEO duality and board meetings impact on financing choice of firms. Panel data covering a five year period from 2012 to 2016 from twenty six listed firms on the Colombo Stock Exchange (CSE) was used. Analysis was done within the Random-effects GLS regression framework. The findings reveal that organizations with larger board sizes employ more debt irrespective of the maturity period in order to raise corporate value. Further, other corporate governance variables such as board independence, CEO duality and board meetings are not found to have a significant impact on short term and long term leverage. The firms should increase their board size for accessing more debt capital as a large board size puts pressure on managers through stringent monitoring and regulatory mechanisms to increase the value of a ﬁrm. However beyond a certain level, further increase in board size could lead to adverse effects. Therefore, this study recommends a policy that may strike a good balance between quality and quantity of board size.
Keywords: Board size; Board independence; CEO duality; Corporate governance; Financing choice